Treatment Technology of Microbial Landscape Aquatic Plants for Water Pollution - Ming Hu; Lei Li (Advances in Materials Science and Engineering)
With the rapid development of industrial and agricultural production, the rapid growth of population, and the acceleration of urbanization, the problem of water pollution is becoming more and more serious. Water shortages and pollution disrupt the balance of ecosystems and seriously limit people’s health and rapid economic development. Nowadays, the method of repairing sewage bodies using microbial landscape aquatic plants is attracting more and more attention, and it is a big challenge to maintain the sustainable development of human beings and nature. This paper uses floating rafts to combine microorganisms and landscape aquatic plants to conduct sewage treatment experiments. According to microorganisms, landscape aquatic plants absorb nutrients in the water body, examine the changes in water quality during the restoration of microorganisms’ landscape aquatic plants, and establish the growth of microorganisms’ landscape aquatic plants. The relationship with changes in water quality aims to provide a theoretical basis for the treatment of slow-flowing water bodies such as lakes, reservoirs, large artificial ponds, and rivers. In this paper, the experiments are divided into four groups (A (experimental sewage + microbial inoculant), B (experimental sewage + plant), C (experimental sewage + microbial inoculant + plant), and D (experimental sewage)). It can be divided into the total nitrogen content, total phosphorus content, and COD value data, and chromaticity detection of each group of the test is continuously monitored weekly to comprehensively detect and observe the repair effect on contaminated water bodies. The experiment proved that the water quality of the three treatment groups was significantly clearer than that of the blank control group, and its clarity: microorganism + plant > microorganism > plant > blank control group. This shows that the combination of microorganisms and landscape aquatic plants can effectively reduce the various pollutants contained in sewage and reduce the color of sewage. Treating sewage using plant technology that combines microorganisms is feasible and promising.